Proposed A Design Performance Management System By Using Knowledge-Based Performance Management System Framework At PT. Marjaya Utama Wisata - Emir Muchamad, Ghiffari (Cv. Syntax Corporation Indonesia, 2024)
Indonesia's tourism sector was hit hard by the COVID-19 pandemic, with a 56% drop in its contribution to the country's GDP (Gross et al.). However, the sector has significantly recovered, with foreign tourist arrivals increasing 119.64% in June 2023 compared to the previous year. In response to this phenomenon, service providers, such as Performance Management Systems (PMS), must implement effective strategies to maximise their potential. PT. Marjaya Utama Wisata (Marjaya Trans), a travel agency based in Bandung, experienced significant growth but experienced fluctuations in revenue and experienced losses in some years. Designing a comprehensive performance management system was necessary to deal with these problems. This research proposes a proposed performance management system using the KBPMS framework. The proposed model was developed by combining a literature review and a case study approach from previous studies applied to the same industry. The analysis was conducted using a qualitative approach and multicriteria decision-making using the Analytic Hierarchy Process (AHP) approach from the management ranks in the company. This research proposes KBPMS with 19 key performance indicators (KPIs) derived from vision, mission, strategy, business processes, and discussions between researchers and the company. From each aspect of the KBPMS, a priority order is generated from the AHP method to see which indicators have a high priority according to the company's management. It is expected that the application of the designed performance management system model can help the company achieve its goals. The development of this model is still in a stage that needs to be further developed. Evaluation and improvement of PMS implementation will be planned on a long-term basis